Study of Transition Region of p-Type SiOx:H as Window Layer in a-Si:H/a-Si1-yGey:H Multijunction Solar Cells - Pei-Ling Chen; Po-Wei Chen; Chuang-Chuang Tsai (International Journal of Photoenergy)
We have studied the p-type hydrogenated silicon oxide (SiOx:H) films prepared in the amorphous-to-microcrystalline transition region as a window layer in a-Si:H/a-Si1-yGey:H multijunction solar cells. By increasing the H2-to-SiH4 flow ratio (RH2) from 10 to 167, the SiOx:H(p) films remained amorphous and exhibited an increased hydrogen content from 10.2% to 12.2%. Compared to the amorphous SiOx:H(p) film prepared at low RH2, the SiOx:H(p) film deposited at RH2 of 167 exhibited a higher bandgap of 2.04 eV and a higher conductivity of 1.15 × 10−5 S/cm. With the employment of SiOx:H(p) films prepared by increasing RH2 from 10 to 167 in a-Si:H single-junction cell, the FF improved from 65% to 70% and the efficiency increased from 7.4% to 8.7%, owing to the enhanced optoelectrical properties of SiOx:H(p) and the improved p/i interface. However, the cell that employed SiOx:H(p) film with RH2 over 175 degraded the p/i interface and degraded the cell performance, which were arising from the onset of crystallization in the window layer. Compared to the cell using standard a-SiCx:H(p), the a-Si:H/a-Si1-yGey:H tandem cells employing SiOx:H(p) deposited with RH2 of 167 showed an improved efficiency from 9.3% to 10.3%, with VOC of 1.60 V, JSC of 9.3 mA/cm2, and FF of 68.9%.